How the weather works : a hands-on guide to our changing climate - Dorion, Christiane; Young, Beverley (Somerville, Mass. : Templar Books, 2011)
An introduction to weather and climate, featuring interactive illustrations and text that explain what makes weather, where rain comes from, why the wind blows, how weather predictions get made, how the global climate has changed over time, and other related topics.
Cover title.
On lift-the-flap, pop-up, pull-tab pages.
Kirkus Review
Kirkus Review, February 2011
5.7
3-6
Keywords: Climatology -- Juvenile literature; Toy and movable books -- Specimens; Weather -- Juvenile literature; Climatology; Toy and movable books; Weather; Climate; Toy and movable books; Weather